Legal Protection of State Land Against Land Encroachment in Indonesia: Normative Ambiguity in Article 502 of the 2023 Criminal Code and a Reformulation Model - Luh Amelia Savitri; Sagung Putri M. E. Purwani (International Journal of Business, Law, and Education, 2026)
This article examines the normative ambiguity embedded in the phrase “right to use state land” in Article 502 of Law Number 1 of 2023 concerning the Indonesian Criminal Code and its implications for the legal protection of state land from land encroachment. State land is not merely an economic asset; under Article 33 paragraph (3) of the 1945 Constitution and the Basic Agrarian Law, it is a public resource that must be administered for the greatest prosperity of the people. Nevertheless, state land remains vulnerable to fraudulent transfer, unlawful occupation, forged documentary claims, informal control, and transactions that exploit administrative delay or weak asset registration. The study applies normative legal research using statutory, analytical, and conceptual approaches. Primary legal materials include the 1945 Constitution, the Basic Agrarian Law, Government Regulation Number 18 of 2021, Government Regulation in Lieu of Law Number 51 of 1960, and Law Number 1 of 2023. The analysis employs systematic and teleological interpretation to assess whether Article 502 can protect state land that has not yet been certified or formally attached to a specific land right. The findings show that Article 502 is progressive because it recognises fraudulent dealings over rights connected with state land, yet its formulation remains insufficiently determinate. The absence of a clear statutory category for “right to use state land” creates interpretive inconsistency, weakens the principle of lex certa, and risks excluding uncertified government assets from criminal-law protection. The article proposes a reformulation model that clarifies the categories of protected state land, synchronises criminal provisions with agrarian law, and integrates asset recovery through an ultimum remedium approach and a double-track system of sanctions and restorative measures.